2018
DOI: 10.1002/ccr3.1584
|View full text |Cite
|
Sign up to set email alerts
|

ApoE isoform leading to hypertriglyceridemia in new onset type 1 diabetes

Abstract: Key Clinical MessageWe report a case of pediatric diabetic ketoacidosis (DKA) with significant hypertriglyceridemia. The patient was found to have the e3/ e4 isoform of ApoE, increasing risk of hypertriglyceridemia in DKA. We suggest further genetic investigation for patients presenting with severe hypertriglyceridemia and DKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…18 Mutation in LPL gene can lead to severe and persistent hypertriglyceridemia in DKA that does not improve with insulin alone. 30 On the other hand, a severe but not persistent hypertriglyceridemia may be caused by abnormality in lipoprotein cofactors. 30 It is possible that subtle abnormality in lipid metabolism in usual conditions may contribute to the development of hyperlipidemia under stress such as DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Mutation in LPL gene can lead to severe and persistent hypertriglyceridemia in DKA that does not improve with insulin alone. 30 On the other hand, a severe but not persistent hypertriglyceridemia may be caused by abnormality in lipoprotein cofactors. 30 It is possible that subtle abnormality in lipid metabolism in usual conditions may contribute to the development of hyperlipidemia under stress such as DM.…”
Section: Discussionmentioning
confidence: 99%
“…30 On the other hand, a severe but not persistent hypertriglyceridemia may be caused by abnormality in lipoprotein cofactors. 30 It is possible that subtle abnormality in lipid metabolism in usual conditions may contribute to the development of hyperlipidemia under stress such as DM. Karagianni et al have reported a case with similar severe hyperlipidemia in DKA.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in insulin deficiency, LPL cannot metabolize lipoproteins and hypertriglyceridemia can occur. It has been suggested that patients with lipemic serum and significant elevations in triglycerides (> 1,495 mg/dL, > 16.9 mmol/L) be considered for further screening for lipid metabolism and structural abnormalities [ 7 ]. Our patient’s family history was negative for dyslipidemia conditions, and genetic testing for disorders of lipid metabolism is being considered.…”
Section: Discussionmentioning
confidence: 99%
“…This results in free fatty acid (FFA) formation and increases in VLDL formation by the liver. 9 In addition to this, insulin normally inhibits ApoC-III expression, which plays a major role in inhibiting lipoprotein lipase (LPL) and hepatic lipase (HL). Insulin deficiency results in decreased hydrolysis and delayed VLDL-TG clearances from plasma.…”
Section: Case Reportmentioning
confidence: 99%
“…It has been suggested by many authors that patients presented with lipemic serum and severe elevations in triglycerides (>1,495 mg/dl, >16.9 mmol/l) should be considered for further screening for lipid metabolism and structural abnormalities. 9 Mild to moderate hypertriglyceridemia is common during episodes of DKA. However, severe hypertriglyceridemia which is defined as a TG level >2,000 mg/dl, is rare.…”
Section: Case Reportmentioning
confidence: 99%